1998
DOI: 10.1021/ma971857s
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chemistry with Macromolecules:  New Self-Assembly based Main Chain Polypseudorotaxanes and Their Properties

Abstract: A new class of main chain polypseudorotaxanes, 8, was prepared by self-assembly of a poly(ester crown ether), poly[bis(5-methylene-1,3-phenylene)-32-crown-10 sebacate] (5), and N,N‘-bis(β-hydroxyethyl)-4,4‘-bipyridinium bis(hexafluorophosphate) (6). The equilibrium constant (K = 58.0 M-1 at 21.8 °C), ΔH (−26.5 kJ/mol) and ΔS (−56.4 J/mol deg)(all averages from several iterative methods) for the formation of 8 were measured by proton NMR spectroscopy. Compared to those (K = 247 M-1 at 21.8 °C, ΔH = −44.7 kJ/mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…3, the electron microscopy images of the xerogel show a nanoribbon morphology which can account for the orthogonal noncovalent interactions to form entangled networks (Fig. 18 Therefore, heating and cooling can result in a reversible gel-sol transition in this obtained supramolecular metallogel (Fig. These results showed that the metal-coordination interactions between the [3]pseudorotaxane and 3 not only achieved the conversion from low-molecular-weight aggregates to the 3D supramolecular polymeric network, but also made an impact on the microscopic nature of the resulting supramolecular metallogel.…”
Section: Communication Dalton Transactionsmentioning
confidence: 99%
“…3, the electron microscopy images of the xerogel show a nanoribbon morphology which can account for the orthogonal noncovalent interactions to form entangled networks (Fig. 18 Therefore, heating and cooling can result in a reversible gel-sol transition in this obtained supramolecular metallogel (Fig. These results showed that the metal-coordination interactions between the [3]pseudorotaxane and 3 not only achieved the conversion from low-molecular-weight aggregates to the 3D supramolecular polymeric network, but also made an impact on the microscopic nature of the resulting supramolecular metallogel.…”
Section: Communication Dalton Transactionsmentioning
confidence: 99%
“…34), reduces the losses from dethreading during the polymerization (Ref. 35), i.e., llK=finite, accounting for the lower degrees of dethreading observed for the polyurethane systems of Type A relative to the analogous polyesters (Scheme 3). Another exciting finding is that it is possible to contol the locus of the crown ether rings in these polyrotaxanes by use of solvent; in CDC1, hydrogen bonding localizes the rings on the urethane moieties, whereas in DMSO the crown ethers are delocalized over other portions of the backbone.…”
Section: B Identification Of Hydrogen Bonding As Driving Force In Fomentioning
confidence: 99%
“…Within this context, benzylammonium, benzimidazolium, and pyridinium cations have been widely used as axles to construct pseudorotaxanes and rotaxanes . Among the most frequently employed wheels are crown ethers, cyclodextrins, cucurbituril, calixarenes, and cyclophanes …”
Section: Introductionmentioning
confidence: 99%
“…Within this context, benzylammonium, benzimidazolium, and pyridinium cations have been widely used as axles to construct pseudorotaxanes and rotaxanes. [15][16][17][18][19][20][21][22][23][24][25][26] Among the most frequently employed wheels are crown ethers, [27][28][29] cyclodextrins, [30,31] cucurbituril, [32][33][34] calixarenes, and cyclophanes. [35][36][37][38] Herein, we report on a novel series of 27-and 29-membered oxaazacyclophanes, which were prepared from aromatic dialdehyde and diamine building blocks and then structurally characterized.…”
Section: Introductionmentioning
confidence: 99%